Cpn60β4 protein regulates growth and developmental cycling and has bearing on flowering time in Arabidopsis thaliana plants. (September 2019) - Tiwari, Lalit Dev; Grover, Anil
Highlights: cpn60β4 mutant plants of Arabidopsis showed faster developmental programming and flowering time. cpn60β4 mutant plants showed larger-sized chloroplasts as against wild type plants. The mutant phenotype was rescued in complemented lines produced using genomic fragment encompassing Cpn60β4 gene. The over-expression of Cpn60β4 gene in wild type plants supported the role of Cpn60β4 gene in regulation of growth processes. Abstract: Chloroplastic Cpn60 proteins are type I chaperonins comprising of Cpn60α and Cpn60β subunits. Arabidopsis genome contains six entries in Cpn60 family, out of which two are for Cpn60α subunit and four for Cpn60β subunit. We noted that the cpn60β4 knockout mutant plants (T-DNA insertion salk_064887 line) differed from the wild type Col-0 plants in the developmental programming. cpn60β4 mutant plants showed early seed germination. Radical emergence, hypocotyl emergence and cotyledons opening were faster in cpn60β4 mutant plants than WT. Importantly, cpn60β4 mutant plants showed early-flowering phenotype. The number of flowers and siliques as well as weight of the seeds were higher in cpn60β4 mutant plants as compared to Col-0 plants. These effects were reverted to wild type like growth and developmental patterns when genomic fragment of Arabidopsis encompassing Cpn60β4 gene was complemented in the mutant background. The overexpression of Cpn60β4 gene using CaMV35 promoter in wild type background (OE-Cpn60β4) delayed the floral transition as against wild type plants. The plastid division were affected in cpn60β4 mutant plants compared to Col-0. The results of this study suggest that Cpn60β4 plays important role(s) in chloroplast development and is a key factor in plant growth, development and flowering in Arabidopsis .